Principal Leadership in Improving the Quality of Educational Facilities and Infrastructure - Rogahang, Heldy Jerry; Makisake, Merdhi Yandeer Jorghie (Jurnal Manajemen Pendidikan Kristen, 2022)
This research aims to determine the influence of a school principal's leadership on the quality of educational facilities and infrastructure at PGRI Enemawira High School, Sangihe Regency. This research uses quantitative regression analysis methods. The sampling technique in this research uses a saturation sample, where the researcher uses the entire research population as the research sample. In obtaining research data, researchers used questionnaire instruments. The data obtained was then analyzed using quantitative regression and multiple linear regression analysis techniques. The results of the research show that: There is no significant influence between the principal's leadership and the quality of educational facilities and infrastructure at PGRI Enemawira High School, Sangihe Regency. The regression equation in this study is Y = 125.877 + 0.031X.